Genome wide association study reveals novel associations with face morphology - Aamer Alshehhi; Mira Mousa; Guan K. Tay; Naoufel Werghi; Habiba AlSafar (PLoS ONE, 2025)
Genome-wide association studies (GWAS) on the Middle Eastern population, including the United Arab Emirates (UAE), have been relatively limited. The present study aims to investigate genotype-face morphology associations in the UAE population through Genome Wide Association Studies (GWAS). Phenotypic data (44 face measurements) from 172 Emiratis was obtained through three-dimensional (3D) scanning technology and an automatic face landmarking technique. GWAS analysis revealed associations of 19 genetic loci with six face features, 14 of which are novel. The GWAS analysis revealed 11 significant relationships between 44 face parameters and 242 SNPs, exceeding the GWAS significance threshold. These phenotypes were previously associated with body height, craniofacial defects, and facial characters. The most significant associations of these genetic variations were related to six main facial features which were facial convexity, left orbital protrusion, mandibular contour, nasolabial angle D, inferior facial angle B, and inferior facial angle A. To the best of our knowledge, this is the first GWAS study to investigate the association of SNP variations with face morphology in the Middle Eastern population.